Cities, saints, and communities in early medieval Europe essays in honour of Alan Thacker - DeGregorio, Scott; Kershaw, Paul; Thacker, Alan 1949- (Studies in the early Middle Ages, 2020)
This book honours the scholarship of English historian Dr. Alan Thacker by exploring the insular, the European and, more broadly, the Mediterranean connections and contexts of the history and culture of Anglo-Saxon England in the age of Bede, and beyond. It brings together original contributions by leading European and North American scholars of Late Antiquity and the early Middle Ages working across a range of disciplines: history, theology, epigraphy, and art history. Moving from the Irish Sea to the Bosporus, this collection presents a linked world in which saints, scholars, and the city of Rome all played powerful connective roles, creating communities, generating relationships, linking east to west, north to south, and present to past